Effective leadership behavior in K-organization / Nadzri Ab. Ghani and Intan Marzita Saidon - Ab. Ghani, Nadzri; Saidon, Intan Marzita (Unit of Research, Development and Commercialization (URDC),UiTM Perlis, 2004)
In entering the new era of K-organizations, having an effective behavior might be a good shield to leaders in facing the unpredictable K-challenges. The purpose of this paper is to point out the traditional view of leadership behavior. On top of that, this paper mentions the need to make the paradigm shift from the traditional view to the transformational leadership behavior. It also highlights few patterns of transformational leadership behavior. Finally, the collaboration of both behaviors with the injection of the Islamic view might provide a new avenue for achieving effective leadership behavior in K-organizations